Continuum Field Model of Street Canyon: Theoretical Description. Part I - Duras, M.M. (Engineering Transactions, 2000)
A general proecological urban road traffic control idea for the street canyon is proposed with emphasis placed on development of advanced continuum field gasdynamical (hydrodynamcal) control model of the street canyon. The continuum field model of optimal control of street canyon is studied. The mathematical physics’ approach (Eulerian approach) to vehicular movement, to pollutants’ emission, and to pollutants’ dynamics is used. The rigorous mathematical model is presented, using gasdynamical (hydrodynamical) theory for both air constituents and vehicles, including many types of vehicles and many types of pollutant (exhaust gases) emitted from vehicles. The six optimal control problems are formulated.